2016
DOI: 10.1590/s1980-5764-2016dn1004005
|View full text |Cite
|
Sign up to set email alerts
|

Gait, posture and cognition in Parkinson's disease

Abstract: Gait disorders and postural instability are the leading causes of falls and disability in Parkinson's disease (PD). Cognition plays an important role in postural control and may interfere with gait and posture assessment and treatment. It is important to recognize gait, posture and balance dysfunctions by choosing proper assessment tools for PD. Patients at higher risk of falling must be referred for rehabilitation as early as possible, because antiparkinsonian drugs and surgery do not improve gait and posture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 55 publications
0
22
0
3
Order By: Relevance
“…One study has shown that gait and balance are impaired in patients with Parkinson's, which can lead to severe falls and injuries (17) . Another study showed that these patients also present this type of risk, therefore, they should be referred to early postural rehabilitation in order to improve gait and accordingly prevent falls (18) . This research identified that auditory deficit is related to the high risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that gait and balance are impaired in patients with Parkinson's, which can lead to severe falls and injuries (17) . Another study showed that these patients also present this type of risk, therefore, they should be referred to early postural rehabilitation in order to improve gait and accordingly prevent falls (18) . This research identified that auditory deficit is related to the high risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we aimed to determine the type of gait (FG, BG, or DG) that is most strongly associated with pathophysiological changes reflecting motor symptoms or the risk of falling in patients with de novo PD. We hypothesized that DG is more closely related to motor symptoms and the risk of falling in PD patients because mild cognitive impairment is not uncommon in the early stages of PD,1213 and such cognitive difficulties could exert a greater impact on DG in patients with de novo PD 14. However, it was found that the results did not fully support this hypothesis.…”
Section: Introductionmentioning
confidence: 95%
“…(e.g., memory loss, word-retrieval difficulties) and behavioral (e.g., depression) symptoms become more tightly coupled as worsening balance and gait deficits increasingly restrict patients' independence and quality of life (Barbosa et al, 2016;Bohnen & Cham, 2006;Dirnberger & Jahanshahi, 2013). Indeed, cognitive resources are necessary to process and integrate sensory and motor information and to plan the motor responses for maintaining balance (e.g., Kelly et al, 2015).…”
mentioning
confidence: 99%